Biocompatibility of submicron Bioglass® powders obtained by a top-down approach - Dörfler, Anja; Detsch, Rainer; Romeis, Stefan; Schmidt, Jochen; Eisermann, Claudia; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2014)
In this study in vitro bioactivity and biocompatibility of two submicron 45S5 Bioglass powders obtained by top-down processing have been evaluated and are compared to the as-received powder. Both submicron powders exhibited flake-like morphologies with lateral extensions of only a few microns; the flake thickness accounted for a few tens of nanometers. Enhanced in vitro bioactivity was found for the comminuted powders upon immersion in simulated body fluid. In vitro biocompatibility was evaluated by incubation of MG-63 osteoblast-like cells with various amounts (0-200 μg/mL) of the glass powders. Neither LDH-activity nor mitochondrial activity (WST-8) tests indicated cell toxicity. Increased mitochondrial activity was found for the submicron powders: incubation with high amounts revealed up to a threefold increase of osteoblast activity (ALP-activity). An overgrowth of the formed mineralized phase with phenotypical MG-63 cells was found by staining only for the submicron glasses. A distance ring is formed for the as-received powder. Superior bioactivity markers are found for shorter process times, that is, lower mass specific surface areas. This is attributed to the formation of carbonates during the comminution process. © 2013 Wiley Periodicals, Inc.
Keywords: in vitro bioactivity and biocompatibility; MG-63 cells; sub-micron particles; top-down production

Enhancing In Vitro Bioactivity of Melt-Derived 45S5 Bioglass® by Comminution in a Stirred Media Mill - Romeis, Stefan; Hoppe, Alexander; Eisermann, Claudia; Schneider, Nadine; Boccaccini, Aldo R.; Schmidt, Jochen; Peukert, Wolfgang (Journal of the American Ceramic Society, 2014)
45S5 Bioglassâ (45S5 BG) is a frequently applied Type A bioactive material, capable of forming an inherent bond to bone and soft tissue. Currently, applied melt-derived bioactive glass powders (BG) exhibit particle sizes between a few to several hundred micrometers. Recent studies on nanometer-sized bioactive glasses (nBGs), produced by bottom-up methods like sol– gel processing or flame spray pyrolysis, have indicated their great potential for several biomedical applications. In this study, the feasibility of top-down processing starting from bulk 45S5 BG by wet comminution in a stirred media mill was investigated. The products were assessed by in vitro hydroxycarbonate apatite (HCAp) formation in simulated body fluid, which is a marker for bioactive behavior. The study reveals the paramount influence of the used solvent for a successful topdown processing: In comparison with the as-received material bioactivity is lost for powders processed in water, preserved for comminution in ethanol and increased for powders processed using the alcohols n-butanol, n-pentanol, and n-hexanol. It was also found that only for the latter solvents, the chemical composition of the glass is maintained during comminution. Flakelike, slightly porous particles with specific surface areas of  25–30 m2/g are obtained. Thus, the presented comminution approach offers a convenient technique to process 45S5 BG with enhanced bioactivity.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.enhanc

Polymeric stabilization of fused corundum during nanogrinding in stirred media mills - Eisermann, Claudia; Mallembakam, Madhusudhan Rao; Damm, Cornelia; Peukert, Wolfgang; Breitung-Faes, Sandra; Kwade, Arno (Powder Technology, 2012)
This paper deals with the steric stabilization of fused corundum during milling in ethanol and water. Different molecular weights of DAPRAL, a block copolymer with lyophilic and lyophobic side chains, were used to stabilize the feed material particles during wet grinding. Preliminary studies of the adsorbed amounts of the polymer in different solvents were determined by TGA and by rheology measurements in order to select sufficient amount of polymer to stabilize the suspension. The median particle size of sterically stabilized milled alumina particles was obtained via Dynamic Light Scattering, Ultrasonic Extinction, BET and SEM. In this investigation primary median particle sizes of 60 nm were obtained in ethanol by applying the steric stabilization mechanism. The mechanochemical characterization was carried out on the milled alumina particles and a phase transformation from alumina to aluminum hydroxide in water was observed, irrespective of stabilization mechanisms. However, no phase transformation was observed in ethanol. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Steric stabilization; Corundum dispersion; DLVO theory; Wet grinding; Adsorption mechanism; Mechanochemical effects

Stabilization of carbon black particles with Cetyltrimethylammoniumbromide in aqueous media - Eisermann, Claudia; Damm, Cornelia; Winzer, Bettina; Peukert, Wolfgang (Powder Technology, 2014)
The stabilization mechanism of aqueous carbon black suspensions by Cetyltrimethylammoniumbromide (CTAB) is studied in this paper. The adsorption of the surfactant CTAB on the carbon black particles was investigated on dried samples by thermogravimetric analyses (TGA), nitrogen adsorption and attenuated total reflection Fourier transformation infrared spectroscopy (ATR-FTIR) as well as in suspension by zeta potential measurements and atomic force microscopy. The particles are stabilized by an adsorbed CTAB monolayer as can be concluded from the results of TGA and of AFM investigations using a liquid cell. Extended DLVO calculations including the steric contribution of CTAB reveal that carbon particles with an adsorbed monolayer of CTAB exhibit sufficient colloidal stability. This result is in qualitative agreement with the experimental results. © 2013 Elsevier B.V.
Keywords: Carbon black; CTAB adsorption; Dispersion; DLVO calculations; Electrosteric stabilization